Improving Outpatientâs Quality of Life Through Patient Adherence of Antihypertensive Therapy Using âMobile Phone (SMS) and Brief Counselingâ5Aâ in Polyclinic of Internal Medicine at PKU Muhammadiyah Bantul Hospital, Yogyakarta - Saputri, Ginanjar Zukhruf; Akrom, Akrom; Darmawan, Endang (Indonesian Journal of Clinical Pharmacy, 2017)
Â The Health-Related Quality of Life (HRQoL) is one of the important psycho-social characteristics that can affect patientâs ability to manage therapy. Poor of knowledge of hypertension and the changing lifestyle can affect the quality of life of patients. One of the pharmacistâs interventions in hypertension management is to conduct counseling. Motivational counseling helps health service to assess patientâs understanding and patientâs readiness to change patientâs behavior. Some motivational counseling methods still need to be developed. Therefore, this study aims to find the influence of the "brief counseling-5A" and "motivational SMS" by a pharmacist on the quality of life and blood pressure control in hypertension patients in the internal disease polyclinic, PKU Muhammadiyah Bantul Hospital, Yogyakarta. The study has been done by using the quasi-experimental method with prospective data collection during the period of January until April 2013. Sixty patients have met inclusion criteria and were divided into two groups. Thirty patients (50%) received "brief counseling-5A" and "motivational SMS" as intervention group and the other thirty patients (50%) received usual care as a control group. The data collection was done by interviewing patients. Medication adherence and QoL were assessed by using Morisky Medication Adherence Scale (MMAS) and SF-36. The values of blood pressure are taken from patientâs medical records. Patientâs quality of life showed a good improvement during post study. It is shown in 8 different domains including pain, fatigue, physical function, emotional function, social function, role physical, mental health, and general health. In intervention group, physical function, emotional function, and pain showed highly significant improvement (p<0.05). Systolic and diastolic blood pressure in the intervention group decreased significantly (p<0.05) (systolic p=0.001 and diastolic p=0.018) in the post study. From this study, it is concluded that the "brief counseling-5A by pharmacist" and "motivational SMS" had a positive impact on patientâs QoL and patientâs blood pressure, hence, the therapy outcome has been achieved.